Effect of Working Capital, Debt Maturity, Sales and Tangibility on Investment Efficiency Listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 Period (Open Society Conference, 2023)
The research objective is to analyze variables such as working capital, debt maturity, sales and tangibility that affect investment efficiency. Investment is an activity of placing funds in one or more types of assets for a certain period to earn income. Factors that reflect company performance are the financial statements presented in the annual report. Underinvestment occurs when an investment company requires the use of large amounts of debt. Companies with overinvestment are companies that are in the mature stage with slow growth rates, and high cash flow. In this study the approach used is using quantitative methods. Then analyzed partial and multiple regression. The data used is secondary data. The independent variables used are working capital, debt maturity, sales, and tangibility. The dependent variable used is investment efficiency. Working capital has no negative and significant effect on investment efficiency. Debt maturity has a negative effect on investment efficiency. Sales have a negative effect on investment efficiency. Firm age has no negative effect on investment efficiency. Tangibility has a negative effect on investment efficiency Working capital does not have a negative effect on investment efficiency. Debt maturity has a negative effect on investment efficiency. Sales have a negative effect on investment efficiency. Tangibility has a negative effect on investment efficiency. Working capital, debt maturity, sales and tangibility effect investment efficiency.